Studi Komparatif Kewenangan Pengadilan TIPIKOR dan Wilayah Mazalim - Huda, Ainul (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
The paper aims to determine and compare the authority of the TIPIKOR court and Wilayah Mazalim Courts in the Islamic judicial system. The results of the study showed the similarity and differences in both judicial systems. The similarity is that they were established specifically to handle and resolve corruption cases. It is their authority, the TIPIKOR Court and Wilayah Mazalim, to settle and solve corruption cases. The differences are that the TIPIKOR Court has a lower level of institutional position than Wilayah Mazalim. It is because of Wilayah Mazalim is equated with the Supreme Court of today. Also, the TIPIKOR Court has a narrower scope of authority than Wilayah Mazalim. The TIPIKOR Court only wields power on corruption cases, whereas Wilayah Mazalim court, apart from handling and settling corruption cases, is also authorized to resolve other cases such as criminal acts.